GAMBARAN FAKTOR RISIKO AKTIVITAS FISIK, KUALITAS TIDUR, DAN STRES DENGAN TEKANAN DARAH PADA MAHASISWA TINGKAT AKHIR FAKULTAS TEKNIK UNIVERSITAS DIPONEGORO - Hany Yuliani; Henry Setyawan Santoso; Mateus Sakundarno Adi; Lintang Dian Saraswati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Hypertension was an increasing of blood pressure in artery. Adolescent who suffered from high blood pressure were likely to undergo it until adulthood. Research in Semarang hypertension in adolescents increase in 2013 (0,04 %) from year 2012 (0.02%). The purpose of this study was describe the factors related with blood pressure at student research in a faculty of engineering Diponegoro University. This study type was descriptive observational with cross sectional design. The population of this study were all students in faculty of engineering Diponegoro University. 100 samples were choosen by using accidental sampling. Descriptive analysis results showed that prevalence of prehypertension systolic 43% dan prehypertension diastolic 61%. Systolic and diastolic prehypertension were mostly found on less physical activity (61,8%), had stress (45,5%), had bad quality of sleep (58,0%)It was concluded that the occurred of hypertension was most suggestion for adolescents were to do physical activity, and enough sleep.